Role of histone post-translational modifications in atherosclerosis and the therapeutic potential of targeting epigenetic modifiers - Wu, Lili; Li, Wei; Ye, Wei (Frontiers in Cell and Developmental Biology, 2025)
Cardiovascular disease (CVD) remains the leading cause of mortality worldwide, with atherosclerosis being the primary pathological substrate underlying most CVD. Epigenetics, defined as a set of regulatory mechanisms that dynamically modulate gene expression patterns or protein functional states through chemical modifications without altering the primary sequence of the genome, has been increasingly recognized as a pivotal driver in the pathogenesis of various diseases. Histone post-translational modifications, such as acetylation, methylation and lactylation, are catalyzed by specific enzymes and are essential for the regulation of gene expression, which in turn influences cellular functions and the progression of diseases. Notably, dysregulation of specific histone modifications is closely associated with the onset and progression of cardiovascular disorders. Accumulating evidence has demonstrated that aberrant histone modifications disrupt vascular cell homeostasis and contribute to atherogenesis by shaping the transcriptional landscape of vascular cells. On the one hand, histone modifications directly influence cellular functions (e.g., endothelial barrier integrity, macrophage lipid phagocytosis, and vascular smooth muscle cell phenotypic switching) and thereby drive atherosclerotic progression. On the other hand, these epigenetic modifications are dynamically modulated by major atherogenic risk factors, including dyslipidemia, pro-inflammatory cytokine release, and hemodynamic stimulation. This review focuses on the multifaceted roles of histone post-translational modifications in mediating vascular dysfunction during atherosclerosis, with an emphasis on the molecular mechanisms linking specific modifications to pathological cellular behaviors. Additionally, we highlight emerging therapeutic strategies targeting histone modification pathways, with the goal of advancing the development of precision diagnostics and interventions for atherosclerosis.